Angiographic anatomy of the extracranial and intracranial portions of the internal carotid arteries in donkeys - Khairuddin, Nurul Hayah; Sullivan, Martin; Pollock, Patrick J. (BioMed Central, 2017)
Background:In horses, the extracranial and intracranial pathway of the internal carotid artery has been described. Theextracranial pathway of the internal carotid artery begins at the carotid termination and runs on the dorsal surface of themedial compartment of the guttural pouch. Thereafter the internal carotid artery passes through the foramen lacerumto continue intracranially, forming part of the rostrolateral quadrants of the cerebral arterial circle (Circle of Willis). Theobjectives of this study were to define and record the anatomy of the carotid arterial tree and the internal carotid arteryin donkeys using angiographic techniques. This is a prospective descriptive study on 26 cadaveric donkeys.Methods:Twenty six donkey cadavers of mixed, age, sex and use presented for reasons unrelated to disease of theguttural pouch were subjected to carotid and cerebral angiography using rotational angiography. Rotationalangiographic and 3 dimensional multiplanar reconstructive (3D-MPR) findings were verified with an arterial latex castingtechnique followed by dissection and photography.Results:The following variations of the carotid arterial tree were identified: [1] the internal carotid and occipital arteriesshared a common trunk, [2] the linguofacial trunk originated from the common carotid artery causing the commoncarotid artery to terminate as four branches, [3] the external carotid artery was reduced in length before giving rise tothe linguofacial trunk, mimicking the appearance of the common carotid artery terminating in four branches, [4] theinternal carotid artery originated at a more caudal position from the common carotid artery termination.Conclusion:Veterinarians should be aware that considerable variation exists in the carotid arterial tree of donkeys andthat this variation may differ markedly from that described in the horse.